Accelerating Africa's structural transformation: lessons from East Asia. - Gabre-Madhin, Eleni Zaude; Johnston, Bruce F. (International Food Policy Research Institute, 1999)
In most countries in sub-Saharan Africa at present, the majority of the population is engaged in agriculture, with economies in the very early stages of structural transformation - the process whereby a predominantly agrarian economy is transformed into a diversified and productive economy dominated by manufacturing and services. These countries are characterized by low levels of farm productivity, limited growth of non-farm employment and high rates of population growth. This paper focuses on the factors involved in fostering a country’s structural transformation. This process of transformation has many dimensions. Among these are emphasized interactions between four factors: increased agricultural productivity, rural industrialization, the expansion of agricultural markets, and the demographic transition. All of these are critical to reducing agriculture’s share in the total labor force and promoting broad-based economic growth. In this paper, the authors assess the relevance of the East Asian experience, primarily that of Taiwan, for the task of determining priorities for agricultural and rural development in the countries of sub-Saharan Africa, in spite of their very different historical and cultural antecedents and physical environments.Important lessons emerging from the East Asian experience are that the transformation of the structure of a predominantly agrarian, semi-subsistence economy cannot be achieved without substantial increases in agriculturalproductivity. Second, the structural transformation process must take advantage of the positive interactions between agricultural and industrial development. These interactions depend on the expansion of the marketed share of agricultural output, which enables farm cash incomes to rise. Finally, they emphasize that demography matters in that increasing the growth of non-farm employment relative to the growth of the total labor force can accelerate structural transformation.